Permasalahan Kurikulum Merdeka dan Dampak Pergantian Kurikulum K13 dan Kurikulum Merdeka - Setioyuliani, Syntia Eka Putri; Andaryani, Eka Titi (Pedagogika: Jurnal Ilmu-Ilmu Kependidikan, 2023)
This research delves into the complexities associated with the implementation of the Independent Curriculum in Indonesia and scrutinizes the repercussions of transitioning from the 2013 Curriculum (K13) to the Independent Curriculum within the educational landscape. Employing a literature review methodology, the study synthesizes insights from diverse literature sources. The findings unveil a spectrum of challenges, encompassing hurdles in effective implementation, the preparedness of educators and students, evaluation of the curriculum's impact on educational quality, as well as its broader social and cultural implications. Despite these challenges, the research identifies positive outcomes, such as a notable surge in student creativity and heightened preparedness for the demands of the professional sphere. This comprehensive exploration contributes nuanced perspectives to the ongoing discourse on curriculum dynamics and their multifaceted influence on the educational paradigm in Indonesia.